Latent Tuberculosis Infection and Subclinical Coronary Atherosclerosis in Peru and Uganda. (3rd January 2021) - Huaman, Moises A; De Cecco, Carlo N; Bittencourt, Marcio S; Ticona, Eduardo; Kityo, Cissy; Ballena, Isabel; Nalukwago, Sophie; Nazzinda, Rashidah; Ticona, Cesar; Azañero, Ruben; Zhang, Bin; Farquhar, Carey; et al.
Abstract: Background: Tuberculosis (TB) has been linked to an increased risk of atherosclerotic cardiovascular disease (ASCVD). We assessed whether latent TB infection (LTBI) is associated with subclinical coronary atherosclerosis in 2 TB-prevalent areas. Methods: We analyzed cross-sectional data from studies conducted in Lima, Peru, and Kampala, Uganda. Individuals ≥40 years old were included. We excluded persons with known history of ASCVD events or active TB. Participants underwent QuantiFERON-TB (QFT) testing to define LTBI and computed tomography angiography to examine coronary atherosclerosis. A Coronary Artery Disease–Reporting Data System (CAD-RADS) score ≥3 defined obstructive CAD (plaque causing ≥50% stenosis). Results: 113 and 91 persons with and without LTBI, respectively, were included. There were no significant differences between LTBI and non-LTBI participants in terms of age (median [interquartile range]; 56 [51–62] vs 55 [49–64] years; P = .829), male sex (38% vs 42%; P = .519), or 10-year ASCVD risk scores (7.1 [3.2–11.7] vs 6.1 [2.8–1.8]; P = .533). CAD prevalence (any plaque) was similar between groups (29% vs 24%; P = .421). Obstructive CAD was present in 9% of LTBI and 3% of non-LTBI individuals ( P = .095). LTBI was associated with obstructive CAD after adjusting for ASCVD risk score, HIV status, and study site (adjusted OR, 4.96; 95% CI, 1.05–23.44; P = .043). Quantitative QFT TB antigen minus Nil interferon-γ responses were associated with obstructive CAD (adjusted OR, 1.2; 95% CI, 1.03–1.41; P = .022). Conclusions: LTBI was independently associated with an increased likelihood of subclinical obstructive CAD. Our data indicate that LTBI is a nontraditional correlate of ASCVD risk. Abstract : We found that latent tuberculosis infection was independently associated with subclinical obstructive coronary artery disease in Peru and Uganda. Our data indicate that latent tuberculosis infection is a nontraditional correlate of atherosclerotic cardiovascular disease risk.